Did Fiscal Stimulus Lift Developing Asia Out of the Global Crisis? An Empirical Investigation - Seok-Kyun Hur; Donghyun Park (East Asian Economic Review (EAER), 2018)
The substantial slowdown of economic growth since the global financial crisis of 2008-2009 is rekindling debate on whether developing Asia should use fiscal expansion to boost aggregate demand. A key factor in the debate is the effectiveness of countercyclical fiscal policy in the region. The global crisis, as well as the fiscal stimulus packages implemented by developing Asian countries at that time, give some clues to this important issue. The region weathered the global crisis well and experienced a robust V-shaped recovery. According to conventional wisdom, the fiscal stimulus packages put in place by Asian governments played a key role in the region's recovery. The central objective of this paper is to empirically test this wisdom by using cross-country panel data. Our main finding is that the stimulus has had a limited but positive impact on developing Asia's output during the global crisis. This lends some support to the notion that countercyclical fiscal policy can help the region cope with severe external shocks. The broader, more fundamental implication for regional policymakers is that the region's long-standing commitment to fiscal discipline can yield significant benefits beyond macroeconomic stability. An important consequence of this commitment relatively healthy fiscal balance sheets - enabled the region's governments to quickly and decisively embark upon fiscal stimulus programs.
Keywords: E32; E62; E63; 330; Fiscal Stimulus; Fiscal Policy; Countercyclical Stabilization; Global Crisis; Developing Asia